PC IN HIV - FROM THEORY TO PRACTICE. REFLECTIONS ON THE PRESENTATION OF A CASE - Cristina Nicolau; Carmen Manciuc; Janny Liviu Prisacaru; Carmen Dorobăt (Romanian Dental Association for Education, 2014)
Introduction Palliative care associates a wide range of therapies designed to ensure the improvement of the quality of life of HIV seropositive patients. Material and methods The evolution of a HIV seropositive patient was analysed, from the time it was detected (2005) until the present time (2009), following dynamically the clinical - immunological and psychological curve. Initial denial of the diagnosis (which caused the late arrival in our department) marked the further progress of the case. The patient required a prolonged period of hospitalisation (45 days), requiring sustained medical support, which involved a multidisciplinary team, joined with psychological counseling of the family, health professionals and representatives of the church. Objectives The need to apply medical and non-medical palliative care, with multidisciplinary implications, establishing a partnership relationship between doctor and patient, important ways to approach the HIV patient. Conclusions The usefulness of integrating concepts, principles and practical rules of palliative care in HIV.